Appendix I to the paper published in transactions of Scientific Journal Physics, 2011 355(16), pages 133 138. - O., Nyamsuren; G. , Ochirbat (Scientific transaction of the National University of Mongolia. Physics, 2022)
A solution of initial value problem for finding amplitude of every field component in arbitrary polarized light waves in totally reflected from self focusing kerr media, as function of dielectric function. is given by power series accurate to the 6th order.